Menjadi Muslim Modern: Konstruksi Identitas Anak Muda Muslim di Kafe - Triantoro, Dony Arung; FZ, Yudhisti Indra (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
This article discusses the construction of the Muslims youth identity in cafes. Cafes as a public habitus that is constructed modern and considered not 'Islamic' does not mean that it has no relationship with Islam. Therefore, this article seeks to answer the question of what is the relationship between Islam, cafes, and social media? So, to what extent do Muslims youth access cafes? Finally, how do Muslims youth construct their identity of piety and youth in a café? To answer these questions, the authors conducted fieldwork in the form of observations and interviews with café owners and several youths with a narrative approach. Then public space theory, identity theory and digital production theory were used to analyze research data. The results of this study found that the relationship between cafes, Islam and social media manifested in the activities of young Muslims themselves, especially in consuming café public spaces such as enjoying food and beverage products, wifi facilities, prayer facilities, and taking pictures. Muslim youth not only access the symbols of café modernity and post them on social media, but also access the café's worship facilities. These three practices, both in consuming symbols of café modernity such as café architectural design and painting art on coffee (latte art), then uploading it to social media and doing prayer practices in cafes are ways for young people to construct their pious and youthful identity while in the café. This finding deconstructs the long-held view by some scholars or the public that cafes are considered public spaces that have no connection with Islam.